Functional Programming in C#, Second Edition - Buonanno, Enrico (Manning Publications, 2022)
Functional Programming in C#, Second Edition teaches functional thinking for real-world problems. It reviews the C# language features that allow you to program functionally and through many practical examples shows the power of function composition, data-driven programming, and immutable data structures. All code examples work with .NET 6 and C# 10.